Genetic Variability and Association Study for Quantitative Traits in Chickpea (Cicer arietinum L.) Genotypes: SHORT COMMUNICATION - Jain, S K; Omprakash; Ritu Sharma; Vaibhav Sharma; Babu Lal Dhaka (Annals of Arid Zone, 2025)
A comprehensive assessment of genetic variability, traits association and direct contribution to yield was conducted at Rajasthan Agricultural Research Institute Durgapura, Jaipur across diverse chickpea genotypes to identify key determinants for yield improvement. Significant genotypic differences were observed for all traits underscoring substantial genetic variability and the scope for selection. The analysis revealed that traits such as grain yield and pods per plant possessed high genetic variability while moderate variability was noted for flowering time, plant height, maturity and test weight. Phenotypic variation exceeded genotypic variation for all traits highlighting the role of environmental factors; however, the narrow gap between them for most traits suggests that environmental influence was limited, making these traits reliable for selection. High broad-sense heritability estimates for the majority of traits, coupled with moderate to high genetic advance, indicated a predominant role of additive gene action, thus making direct selection effective for improving key traits associated with yield. Correlation analysis revealed positive association of yield with flowering time, plant height, maturity and pods per plant while negative association was observed with plant stand at harvest. Path coefficient analysis provided deeper insights into the nature of trait-yield relationships. Flowering time, pods per plant and test weight exerted strong direct positive effects on yield suggesting their strategic importance in breeding programs. Conversely, maturity, plant height and plant stand at harvest showed negative direct effects, indicating potential yield penalties associated with these traits. The relatively low residual effect highlights the robustness of the model, confirming that the selected traits effectively explain the majority of yield variation and offer promising avenues for genetic enhancement in chickpea.